Essays on Information Consumption and Dissemination on Digital Social Platforms - Puthineedi, Venu Bhaskar (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2025)
The increasing influence of digital social platforms on public opinion, political polarization, and information trust poses significant challenges for society, governance, and platform design. This research investigates the cognitive, emotional, and systemic mechanisms that shape how individuals consume and disseminate information in these environments, offering a multidimensional perspective through three interrelated essays. The first essay introduces cognitive friction as a novel mechanism to disrupt echo chambers by leveraging cognitive dissonance. A controlled experiment demonstrates that this intervention reduces passive engagement with belief-reinforcing content and fosters reflective processing moderated by users' political orientation and personality traits. The second essay examines the early formation of opinions in high-volume, unverified information ecosystems. Two experimental studies reveal that user beliefs consolidate after minimal exposure and are heavily influenced by superficial digital identity cues -such as academic-sounding titles-over verified expertise, highlighting critical vulnerabilities in digital trust. The third essay explores the emotional dynamics of political discourse on Reddit. Using advanced sentiment and emotion analysis on a large dataset, the study shows that negative emotions -particularly anger and fear- combined with multimedia elements significantly enhance engagement and virality. These patterns demonstrate how design and algorithmic affordances shape the emotional intensity and reach of political narratives. Together, these essays contribute to the Information Systems literature by elucidating the psychological and structural drivers of digital discourse. The findings offer actionable insights for platform governance, content moderation, and the development of responsible digital ecosystems.
APPROVED
Keywords: Echo chambers; Cognitive friction; Opinion formation; Social media platforms; Digital Identity